From racial prejudice to cyber-racism perpetration: the effects of the dark tetrad, anonymity perceptions, and the dimensions of online disinhibition - Scott, Jordan E. (My University, 2026)
Cyber-racism is online communication that negatively targets another’s race. This behavior has a negative impact on victim’s mental health and there has been little research conducted on the perpetration of this act. The current research aimed to integrate prejudice theory and cyber-racism specific theory to gain a more encompassing understanding of cyber-racism perpetration. The two current studies further aimed to extend cyber-racism research by identifying personality variables that may explain individual difference in cyber-racism perpetration. Study 1 examined how the Dark Tetrad moderates the serial mediating influence of anonymity and online disinhibition in the relationship between racial prejudice and cyber-racism. Results suggest that anonymity and online disinhibition serially mediate the relationship between racial prejudice and cyber-racism perpetration, especially for those high in Dark Tetrad traits. Study 2 investigated whether specific aspects of online disinhibition impact the integrated cyber-racism model and how the Dark Tetrad moderate these relationships. Results suggest that online disinhibition may work more efficiently as a whole construct, as no sub-dimension of online disinhibition serially mediated the integrated cyber-racism model. This program of research provided important information on how individual differences and specific nuances of online disinhibition influence an integrated cyber-racism model as well as practical implications in terms of who is most likely to perpetrate cyber-racism and in what situations. By better understanding the situations and individual differences in which cyber-racism is most likely, we may be able to limit the negative impacts on victims and perpetrators.
Keywords: Prejudice; Dark Tetrad; Anonymity; Online